Aniba rosaeodora (Var. amazonica Ducke) Essential Oil: Chemical Composition, Antibacterial, Antioxidant and Antitrypanosomal Activity - Amanda Mara Teles; João Victor Silva-Silva; Juan Matheus Pereira Fernandes; Kátia da Silva Calabrese; Ana Lucia Abreu-Silva; Silvio Carvalho Marinho; Adenilde Nascimento Mouchrek; Victor Elias Mouchrek Filho; Fernando Almeida-Souza (MDPI AG, 2020)
Aniba rosaeodora is one of the most widely used plants in the perfumery industry, being used as medicinal plant in the Brazilian Amazon. This work aimed to evaluate the chemical composition of A. rosaeodora essential oil and its biological activities. A. rosaeodora essential oil presented linalool (93.60%) as its major compound. The A. rosaeodora essential oil and linalool showed activity against all the bacteria strains tested, standard strains and marine environment bacteria, with the lower minimum inhibitory concentration being observed for S. aureus. An efficient antioxidant activity of A. rosaeodora essential oil and linalool (EC50: 15.46 and 6.78 µg/mL, respectively) was evidenced by the inhibition of the 2,2-azinobis- (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical. The antitrypanosomal activity of A. rosaeodora essential oil and linalool was observed at high concentrations against epimatigote forms (inhibitory concentration for 50% of parasites (IC50): 150.5 ± 1.08 and 198.6 ± 1.12 µg/mL, respectively), and even higher against intracellular amastigotes of T. cruzi (IC50: 911.6 ± 1.15 and 249.6 ± 1.18 µg/mL, respectively). Both A. rosaeodora essential oil and linalool did not exhibit a cytotoxic effect in BALB/c peritoneal macrophages, and both reduced nitrite levels in unstimulated cells revealing a potential effect in NO production. These data revealed the pharmacological potential of A. rosaeodora essential oil and linalool, encouraging further studies.